Pharmacoeconomic aspects of the treatment of pituitary gland tumours - Sowiński, Jerzy; Sawicka, Nadia; Piątek, Katarzyna; Zybek, Ariadna; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2013)
Nowadays physicians are under economic pressure; therefore therapeutic decisions based on safety, efficacy, and the effectiveness of the medication also require economic analysis. The aim of this review is to discuss data concerning the cost-effectiveness of drug therapy in patients with hormonally active pituitary adenomas, namely growth hormone, adrenocorticotropic hormone, thyroid-stimulating hormone-secreting pituitary adenomas, prolactinoma and pituitary incidentaloma. In acromegalic patients using lanreotide is cheaper for health care payers and more convenient for physicians and patients because of the opportunity for self/partner injections, lower clogging risk and possibility of longer intervals between injections, while the efficacy is comparable with octreotide. Patients with prolactinomas should be treated with novel dopamine agonists, such as cabergoline or quinagolide, however, bromocriptine still remains a cheaper and almost as effective alternative. There are no easy methods or algorithms, but in general, extracting the maximum value from the investment in treatment is essential.